Asymmetric Cascaded Inverter for Photovoltaic Applications Based on Carrier Redistribution Modulation Strategies - Rao, S. Nagaraja; Biradar, Ambresh G.; S, Sachin (International Journal of Engineering and Technology, 2018)
Asymmetric Cascaded Multilevel inverter (ACMLI) for photovoltaic (PV) generating system is presented in this paper. The proposed asymmetrical arrangements of seven-level cascaded inverters have been compared with advanced modulation strategies, in order to find an optimum arrangement with lower harmonic distortion and optimized output voltage quality and which makes use of minimum number of switches to get more levels. It also reduces the complexity, number of sources, cost and losses. Modulating control techniques can be modified in two ways, namely Modified Carrier (MC) and Modified Reference (MR). This paper proposes modifies space vector based pulse width modulation (PWM) using various U-type Carrier Redistribution Methods (CRM) which utilize the control freedom degree (CFD) of vertical offsets among carriers and also compared with existing sinusoidal PWM technique for single-phase seven level ACMLI using MATLAB/Simulink.